Moralność i pytanie o Boga - Brzózy, Zbigniew Nikodem (Wydział Teologiczny UAM, 2009)
The article gives a synthetic overview of the relevance of the problem of God for the discourse on man. The question about God is not just one of a number of particular questions raised by the human mind. It is something basic because it has to do with the ultimate sense or nonsense of human life. Neither is it just a theoretical question, since it conditions the ethical dimension of the human life and ties morality with the need of justice. A complete understanding of man calls for a metaphysics that asks the question about God. The article refers to the texts of such philosophers as Plato, Aristotle, Anselm of Aosta, Thomas Aquinas, Descartes, Blaise Pascal, Immanuel Kant, Emmanuel Lévinas. Other cited authors include: St. Augustine, St. John of the Cross and contemporary poets: Wis3awa Szymborska and Hans Magnus Enzensberger.
Morality and the Question about God
Keywords: anthropology and bioethics; pragmatic ethics; moral intellectualism; ethos and logos